A critical account of English syntax : grammar, meaning, text - Brown, E. K.; Miller, J. E. (James Edward), 1942- (Edinburgh textbooks on the English language. Advanced., 2016)
Tackling the role of syntactic constructions in text, this textbook brings out the connections between syntactic structures and semantics/pragmatics and the function of different clausal structures in written and spoken texts. It also draws attention to variation in standard written English, to the grammatical structures and discourse devices in spoken English, and to ongoing changes in English grammar. It focuses on the concepts of descriptive grammar as extended and refined over the last fifty years. This is a practical yet flexible reference that you can return to again and again, whether it be for learning, research or teaching.